2020
DOI: 10.21037/cdt.2019.06.02
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance imaging for structural heart disease

Abstract: Cardiovascular magnetic resonance (CMR) has increasingly become a powerful imaging technique over the past few decades due to increasing knowledge about clinical applications, operator experience and technological advances, including the introduction of high field strength magnets, leading to improved signal-to-noise ratio. Its success is attributed to the free choice of imaging planes, the wide variety of imaging techniques, and the lack of harmful radiation. Developments in CMR have led to the accurate evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Photograph shows specialized goggles (arrow), resting on an MRI table, which allow a child to view a movie during the exam to improve the experience pediatric cardiac MRI is performed for cardiomyopathy (to include myocarditis and viability studies) or CHD (encompassing valvular heart disease and aortopathies along with shunts and complex lesions) [28]. In cardiomyopathy, the main objectives are to establish cardiac morphology, ventricular volumetry/function ± mass, and myocardial tissue characterization [29]. In CHD, the exam generally includes an assessment of intracardiac and extracardiac anatomy and any complicating features (either presurgical or postoperative), ventricular volumetry/function ± mass, valvular function, and pertinent vascular flow measurements [30].…”
Section: Protocol Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Photograph shows specialized goggles (arrow), resting on an MRI table, which allow a child to view a movie during the exam to improve the experience pediatric cardiac MRI is performed for cardiomyopathy (to include myocarditis and viability studies) or CHD (encompassing valvular heart disease and aortopathies along with shunts and complex lesions) [28]. In cardiomyopathy, the main objectives are to establish cardiac morphology, ventricular volumetry/function ± mass, and myocardial tissue characterization [29]. In CHD, the exam generally includes an assessment of intracardiac and extracardiac anatomy and any complicating features (either presurgical or postoperative), ventricular volumetry/function ± mass, valvular function, and pertinent vascular flow measurements [30].…”
Section: Protocol Developmentmentioning
confidence: 99%
“…Cine images facilitate qualitative assessment of regional and global biventricular function. In addition, biventricular volumes and ejection fractions can be quantified by tracing biventricular endocardial contours (and epicardial contours, if myocardial mass measurements are needed) in end-diastole and end-systole using dedicated software [29,32]. LGE imaging allows for identification of areas of myocardial inflammation or fibrosis.…”
Section: Protocol Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies suggest that CMR continues to have a unique advantage for detecting cardiac function ,and assessing focal and diffuse myocardial brosis [8]. Late gadolinium enhancements (LGEs) of CMR imaging for detecting myocardial brosis have a distinct advantage over other methods; however, a recent study has shown that gadolinium might be deposited in the skin, dentate nucleus, and globus pallidus of patients with normal renal function [9] .. Studies have shown that non-contrast-enhanced cardiac cine MRI was able to identify myocardial strain, a sensitive indicator of early cardiovascular dysfunction [10][11]. Non-contrast-enhanced cardiac cine MRI is a standard cardiac MRI examination method that can obtain end-diastolic volume index (EDVi) evaluations of left ventricular volume changes, myocardial mass index (Myo Mass) evaluations of overall quality changes, and mass-to-volume rate (MVR) evaluations of concentric circular remodeling of left ventricular myocardia [12].…”
Section: Introductionmentioning
confidence: 99%